Food safety versus food security in a world of famine - IOANA MIHAELA BALAN; ALIN COSMIN POPESCU; TIBERIU IANCU; GABRIELA POPESCU; CAMELIA TULCAN (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The purpose of this article is to discuss the tension that can arise when trying to ensure food safety, which is governed by ever-stricter regulations, and food security, which is a top priority objective of global security and the security of each state. These legal food safety regulations, which can be exaggerated in some cases, are contributing to the already severe famine of food waste to the detriment of the starving population on Earth. The study aims to shed light on how the stricter regulations for food safety and food security have impacted the situation.Method: Specific characteristics of the European Union were presented in the current research using a case study approach, although they are applicable globally. The selection of the study unit, or Romania as a member of the European Union, and its delimitation are emphasised at the expense of factors relevant to the research methodology.Findings: According to the results, the term "food waste" does not include scraps left over after consumers have finished eating or debris from improperly storing perishables. Paradoxically, this waste has manifested itself in a heightened focus on their own safety, as evidenced by stricter regulations surrounding food handling. Maximum allowable concentrations for various contaminants are constantly in flux, with some shifts being nothing more than the selfish expression of extreme care and concern by people in developed nations.Implications/Novel Contribution: As if the moral and financial costs of food waste weren’t enough, doing so also has a detrimental effect on the planet’s finite resources. According to the study’s results, everyone involved in food production, distribution, and consumption should do their part to minimize food loss and waste. Farmers, food manufacturers, and processors can all learn from the study’s results, as can those in the hospitality industry, grocery stores, other retailers, and consumers.